2022
DOI: 10.5603/fm.a2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperglycaemia on the macrophages in the cell culture

Abstract: Background: The availability of glucose in tissue has a role in macrophages polarization into an inflammatory phenotype. The over nutrition condition such as hyperglycemia induces macrophage infiltration especially the inflammatory macrophages. The aim of this study is to analyse the effect of hyperglycemia condition on cytokines production by human monocytes-derived macrophages. Materials and methods: Monocyte cells that obtained from peripheral blood mononuclear cells isolation from donors were incubated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A growing and important number of investigations have shown that the function of the immune system is altered in DM, with hyperglycemia being one of the factors responsible for this dysfunction [ 79 , 80 , 81 , 82 , 83 , 84 ]. Hyperglycemia can modify the activity of various leukocytes, including monocytes/MΦs [ 85 , 86 ]. Both in vitro and in vivo studies indicate that chronic hyperglycemia increased polarization of M2 MΦs in diabetic mice and in bone marrow-derived MΦs exposed to high glucose concentrations [ 79 , 87 , 88 ], which would contribute to the progression of tissue fibrosis in DM.…”
Section: Discussionmentioning
confidence: 99%
“…A growing and important number of investigations have shown that the function of the immune system is altered in DM, with hyperglycemia being one of the factors responsible for this dysfunction [ 79 , 80 , 81 , 82 , 83 , 84 ]. Hyperglycemia can modify the activity of various leukocytes, including monocytes/MΦs [ 85 , 86 ]. Both in vitro and in vivo studies indicate that chronic hyperglycemia increased polarization of M2 MΦs in diabetic mice and in bone marrow-derived MΦs exposed to high glucose concentrations [ 79 , 87 , 88 ], which would contribute to the progression of tissue fibrosis in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that a hyperglycemic condition activates the production of IL-1, IL-6, and TNF-𝛼 [39][40][41] . All these in ammatory factors have been reported to be related to secondary axonal injury.…”
Section: Discussionmentioning
confidence: 99%